SUSTAINABLE DEVELOPMENT GOALS IN INDONESIA'S POST-PANDEMIC ECONOMIC DEVELOPMENT: SUSTAINABLE DEVELOPMENT GOALS DALAM PEMBANGUNAN EKONOMI INDONESIA PASCA PANDEMI - Arta Rusidarma Putra; Suflani Suflani (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2022)
The Sustainable Development Goals (SDGs) are a global development agreement that is very important to deal with very high and constantly changing economic conflicts such as the impact of strong political interests and foreign intervention. This study aims to examine how the Sustainable Development Goals approved by the United Nations in 2015 have an impact on Indonesia, especially in the economic sector. This study uses the literature study method to describe international economic conditions that have an impact on economic conditions in Indonesia through the results of research that has been conducted in several countries, especially in Asia. The research results show that a number of innovations and policies are needed in order to achieve the SDGs in the field of economic growth and employment. One of the strategies is to create a digital economy platform that uses the principle of collaboration from all parties and strengthens the management of policies, infrastructure and the consumer sector. This rationale is inseparable from the strong foreign intervention which is a consequence of the state debt which always increases every year